2016
DOI: 10.1073/pnas.1509612113
|View full text |Cite
|
Sign up to set email alerts
|

Mushrooms use convectively created airflows to disperse their spores

Abstract: Thousands of basidiomycete fungal species rely on mushroom spores to spread across landscapes. It has long been thought that spores depend on favorable winds for dispersal-that active control of spore dispersal by the parent fungus is limited to an impulse delivered to the spores to carry them clear of the gill surface. Here we show that evaporative cooling of the air surrounding the pileus creates convective airflows capable of carrying spores at speeds of centimeters per second. Convective cells can transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 24 publications
4
66
0
Order By: Relevance
“…In theory, the initial phase of spore dispersal of some basidiomycete mushroom-forming species involves the discharge of basidiospores from the gill by a mechanism promoted by a droplet, also known as a Buller's drop (26), which is normally stimulated by the secretion of mannitol and other sugars (27). Then, convective airflows promoted by the pileus enhance the vertical movement of these spores, which may then reach dispersive winds (28). Finally, these spores may fall by gravity or rainfall events.…”
Section: Discussionmentioning
confidence: 99%
“…In theory, the initial phase of spore dispersal of some basidiomycete mushroom-forming species involves the discharge of basidiospores from the gill by a mechanism promoted by a droplet, also known as a Buller's drop (26), which is normally stimulated by the secretion of mannitol and other sugars (27). Then, convective airflows promoted by the pileus enhance the vertical movement of these spores, which may then reach dispersive winds (28). Finally, these spores may fall by gravity or rainfall events.…”
Section: Discussionmentioning
confidence: 99%
“…The role of macrofungi as a strong source of fungal spores in the atmosphere has been investigated using the Gaussian plume model (GPM) [44,45] for standard atmospheric conditions. Here, it is assumed that the source (a spore emission rate of 540 spores cm -2 s -1 [46]) is located 10 cm above the ground and that the spore concentrations were derived within a vicinity of 100 m and up to a height of 10 m (PM 10 sampling was performed at a height of 10 m in the same location during the same study period; however, the PM 10 results are not shown here).…”
Section: Methodsmentioning
confidence: 99%
“…To estimate the concentration, we set the following conditions: (i) the fruiting body height as 10 cm from the ground, (ii) an average spore size of 3 μm, (iii) an initial spore release rate of Q = 540 spores cm -2 s -1 [46], and (iv) an average wind speed of 1.79 m/s (the average wind speed observed during the sampling period). The following steps were conserved in the dispersal estimation: (i) estimating the settling velocity, V s , [45] (S1 Text); (ii) estimating the rate of convective airflow in terms of the gravity current, U g [46]; and (iii) estimating the presence of spores in terms of their concentration for a fixed height (10 m) using GPM [44].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations